The EFFECTS OF LEARNING MEDIA AND VOCABULARY MASTERY TOWARDS READING ENGLISH TEXT SKILL - Yusuf Hekmatiar; Chotibul Umam (FKIP, Universitas Banten Jaya, 2020)
The purpose of this researce is to find out the effect of learning media towards reading English text skill, the effect of vocabulary mastery towards reading English text skill, the interaction effects of learning media and vocabulary mastery towards reading English text skill. The research methodology that is used in this research is experiment by giving different types of treatment to two student learning groups. The sample is 44 students, consist of 22 experimental class students and 22 control class students, with the sampling technique in this study being intact class based on Factorial Group Design. Data analysis used descriptive statistical method, normality test, homogeneity test, and two-way ANOVA. This research was conducted in the even semester of 2019/2020 academic year, October - November 2019. The results of the study showed: 1) There is significant effect of learning media towards reading English text skill, It is proved by the value of Sig. = 0,000 < 0,05 and F0 = 64,015. 2) There is significant effect of vocabulary mastery towards reading English text skill, It is proved by the value of Sig. = 0,000 < 0,05 and F0 = 6,682. 3) There are no significant interaction effects of learning media and vocabulary mastery towards reading English text skill, It is proved by the value of Sig. = 0,183 > 0,05 and F0 = 1,833.